2012
DOI: 10.1371/journal.pone.0031029
|View full text |Cite
|
Sign up to set email alerts
|

Towards the “Baby Connectome”: Mapping the Structural Connectivity of the Newborn Brain

Abstract: Defining the structural and functional connectivity of the human brain (the human “connectome”) is a basic challenge in neuroscience. Recently, techniques for noninvasively characterizing structural connectivity networks in the adult brain have been developed using diffusion and high-resolution anatomic MRI. The purpose of this study was to establish a framework for assessing structural connectivity in the newborn brain at any stage of development and to show how network properties can be derived in a clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
75
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(79 citation statements)
references
References 37 publications
4
75
0
Order By: Relevance
“…With all major white matter tracts being in place by the end of normal gestation, it is not surprising that structural connectome studies -examining whole brain connectivity on a macroscopic level (Box 1) -have revealed structural network organization in the neonatal brain to show great similarity to the adult human brain Brown et al, 2014;Ratnarajah et al, 2013;Shi et al, 2012;Tymofiyeva et al, 2012;van den Heuvel et al, 2014;Yap et al, 2011). Key features of adult connectome architecture have been demonstrated in the neonatal brain, including a small world organization -combining local specialization with long-range efficiency -, a modular topology -meaning that the network constitutes smaller subnetworks for specialized information processing -, and a heavy tailed degree distribution with brain regions which show the highest number of connections forming a central core or 'rich club' (Box 1).…”
Section: Postnatal Brain Developmentmentioning
confidence: 99%
“…With all major white matter tracts being in place by the end of normal gestation, it is not surprising that structural connectome studies -examining whole brain connectivity on a macroscopic level (Box 1) -have revealed structural network organization in the neonatal brain to show great similarity to the adult human brain Brown et al, 2014;Ratnarajah et al, 2013;Shi et al, 2012;Tymofiyeva et al, 2012;van den Heuvel et al, 2014;Yap et al, 2011). Key features of adult connectome architecture have been demonstrated in the neonatal brain, including a small world organization -combining local specialization with long-range efficiency -, a modular topology -meaning that the network constitutes smaller subnetworks for specialized information processing -, and a heavy tailed degree distribution with brain regions which show the highest number of connections forming a central core or 'rich club' (Box 1).…”
Section: Postnatal Brain Developmentmentioning
confidence: 99%
“…Some other recent works have focused on the examination of the structural connectome of young infants by performing tractography between numerous anatomical regions in the brain [3,41,50,52,53,58,54]. Takahashi et al examined results of full-brain tractography qualitatively and described trends across postmortem infants between 17 and 40 weeks [50].…”
Section: Introductionmentioning
confidence: 99%
“…Yap et al examined the development of connectomes in young children, across a range of ages between 2 weeks and 2 years, using measures of network integration and segregation [58]. Tymofiyeva et al used an atlas-free approach to analyze connectome development in preterm infants, children and adults, also employing network measures to capture topological changes [52,53]. Very recently, Ball et al studied a specific network measure known as rich-club organization in a cohort of preterm infants [2].…”
Section: Introductionmentioning
confidence: 99%
“…Brainnetome has sparked promising research and clinical applications for both developmental and neuropsychiatric conditions [2,[5][6][7][8][9] . The emerging Brainnetome era needs multidisciplinary collaboration [12] .…”
Section: Future Directions Of Dmri For Brainnetomementioning
confidence: 99%
“…To date, it is the only non-invasive method for revealing the micro-geometry of nervous tissues and exploring white matter fiber connectivities in living human subjects. Increasing numbers of reports reveal altered networks of white matter microstructure (WMM) in neuropsychiatric disorders, such as MDD [4] , bipolar disorder [15] , AD [16] , schizophrenia [17] and epilepsy [18] , as well as in development [7,8] and healthy aging [9] .…”
mentioning
confidence: 99%